Side effects of COVID-19 vaccines in paediatric patients: a review systematic and meta-analysis protocol - Freitas, Cijara Leonice; Sarmento, Ayane Cristine Alves; Serquiz, Nicoli; Nobre, Maria Luisa; Costa, Ana Paula Ferreira; Medeiros, Kleyton Santos; Gonçalves, Ana Katherine (BMJ open, 2024)
IntroductionThe paediatric population represents a quarter of the world’s population, and like adult patients, they have also suffered immeasurably from the SARS-CoV-2 pandemic. Immunisation is an effective strategy for reducing the number of COVID-19 cases. With the advancements in vaccination for younger age groups, parents or guardians have raised doubts and questions about adverse effects and the number of doses required. Therefore, systematic reviews focusing on this population are needed to consolidate evidence that can help in decision-making and clinical practice. This protocol aims to assess the safety of COVID-19 vaccines in paediatric patients and evaluate the correlation between the number of vaccine doses and side effects.Methods and analysisWe will search the PubMed, ClinicalTrials.gov, Web of Science, Embase, CINAHL, Latin American and Caribbean Health Sciences Literature, Scopus and Cochrane databases for randomised and quasi-randomised clinical trials that list the adverse effects of the COVID-19 vaccine and assess its correlation with the number of doses, without any language restrictions. Two reviewers will select the studies according to the inclusion and exclusion criteria, extract data and asses for risk of bias using the Cochrane risk-of-bias tool. The Review Software Manager (RevMan V.5.4.1) will be used to synthesise the data. We will use the Working Group’s Grading of Recommendations Assessment, Development and Evaluations to grade the strength of the evidence of the results.Ethics and disseminationFormal ethical approval is not required as no primary data are collected. This systematic review will be disseminated through a peer-reviewed publication.PROSPERO registration numberCRD42023390077.